Recommendations for policy action to the Secretary of Agriculture and Ministry agencies in Bangladesh, and policy advice to decision makers in India, Mexico and Nigeria - CGIAR Research Program on Wheat (2020)
WHEAT and MAIZE scientists, as part of a multi-Center + international partners (FAO) initiative in Bangladesh, provided recommendations for policy action to the Secretary of Agriculture and Ministry line agencies. This has positioned the CGIAR in Bangladesh as a "go-to" for advice to Government on COVID response. With other partners, WHEAT and MAIZE scientists provided ex ante, foresight and prioritisation advice to decision-makers in India, Mexico and Nigeria, informing policy action.